Environmental monitoring program to support food microbiological safety and quality in food industries: A scoping review of the research and guidelines. (December 2021) - De Oliveira Mota, Juliana; Boué, Géraldine; Prévost, Hervé; Maillet, Aurélien; Jaffres, Emmanuel; Maignien, Thomas; Arnich, Nathalie; Sanaa, Moez; Federighi, Michel
Abstract: Background: Food safety and quality can be compromised by microbiological contamination caused by a variety of pathogenic and spoilage microorganisms present in the production environment. The combination of monitoring both food products and the production environment is a lever to increase food safety and quality. Environmental monitoring programs (EMPs) implemented in food industries allow evaluating the clout of the microbial controls in food processing plants. Scope and approach: The aim of the present review is to systematically assess, using the Scoping review and PRISMA method, available information and strategies to build efficient EMP in the food industry. Key findings and conclusions: Despite the available literature on the implementation of EMPs, there is to date no ready-to-use method and its application strongly depends on the characteristics of the processing plant. A common three-step approach has been proposed for the construction of EMP, whatever the food sector including a pre-analytical, an analytical and a post-analytical step. The pre-analytical step aims to design strategies for the implementation of efficient EMP, considering the hazards and the risk associated with food product and food plant. The analytical step consists of sampling stages using cultural or molecular approaches. Finally, the post-analytical step, concerns the management of data collected. EMPs are dynamic programs that undergo change over time and must be updated on a regular basis in order to guarantee their fit for purpose. Highlights: Environmental Monitoring Programs (EMPs) are essential for food safety and quality. Ready-to-use and fit-in-all methodology are not available to date. Communication on practices in food industries are needed to improve their EMPs. A three-step methodology is proposed for a structured and harmonized application.